Athlete Identity in Social Media: The Effect of Online Identity Construction on Social Media Addiction and Self-Esteem in University Students - Ergün, Zuhal (Ataturk Universitesi, 2025)
This study aims to examine the relationship between online identity construction, social media addiction and self-esteem levels of university students who are active in sports. In the study, a quantitative research design was created using descriptive and relational survey model and data were collected from 288 licensed student-athletes studying at the Faculty of Sports Sciences. Data collection tools included Online Identity Construction Scale, Social Media Addiction Scale and Rosenberg Self-Esteem Scale. The findings of the study show that there is a significant and positive relationship between online identity construction and social media addiction. This situation reveals that as students construct their athlete identities in online environments, they tend to use social media more. On the other hand, no significant relationship was found between online identity construction and self-esteem. A negative and significant relationship was found between social media addiction and self-esteem, indicating that an increase in social media addiction may decrease self-esteem levels. Regression analysis results show that social media addiction and self-esteem variables explain 18.9% of the total variance in online identity construction. In this process, social media addiction stands out as a stronger predictor. The results reveal that university student athletes' identity construction processes on social media are closely related to their digital interaction levels, but these processes do not have a direct effect on self-esteem.